2020
DOI: 10.1371/journal.pone.0237283
|View full text |Cite
|
Sign up to set email alerts
|

Fate of antibiotic resistant E. coli and antibiotic resistance genes during full scale conventional and advanced anaerobic digestion of sewage sludge

Abstract: Antibiotic resistant bacteria (ARB) and their genes (ARGs) have become recognised as significant emerging environmental pollutants. ARB and ARGs in sewage sludge can be transmitted back to humans via the food chain when sludge is recycled to agricultural land, making sludge treatment key to control the release of ARB and ARGs to the environment. This study investigated the fate of antibiotic resistant Escherichia coli and a large set of antibiotic resistance genes (ARGs) during full scale anaerobic digestion (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…It is worth noting that the abundance of various ARGs was within the range of absolute abundance of ARGs about 10 4 to 10 10 copies per gram of sludge reported for digestate from full-scale sludge mesophilic AD in the literature. 52,53 Overall, the total copies of ARGs for the microaeration and iron-dosed reactors were 8.8 × 10 4 and 9.1 × 10 4 per gram of sludge which was significantly lower (p-value = <0.001) than the control (1.2 × 10 5 gene copies/g sludge) (Figure 5). Analogous to ARGs, MGEs (intl1 and intl2) also showed similar patterns, i.e., substantially higher levels (p-value = <0.001) in the control than in test reactors.…”
Section: ■ Materials and Methodsmentioning
confidence: 94%
“…It is worth noting that the abundance of various ARGs was within the range of absolute abundance of ARGs about 10 4 to 10 10 copies per gram of sludge reported for digestate from full-scale sludge mesophilic AD in the literature. 52,53 Overall, the total copies of ARGs for the microaeration and iron-dosed reactors were 8.8 × 10 4 and 9.1 × 10 4 per gram of sludge which was significantly lower (p-value = <0.001) than the control (1.2 × 10 5 gene copies/g sludge) (Figure 5). Analogous to ARGs, MGEs (intl1 and intl2) also showed similar patterns, i.e., substantially higher levels (p-value = <0.001) in the control than in test reactors.…”
Section: ■ Materials and Methodsmentioning
confidence: 94%
“…In untreated sludge, Redhead et al [ 72 ] found higher resistance of E. coli isolates to amoxicillin, trimethoprim, ciprofloxacin, and gentamicin. After thermal hydrolysis at WWTPs, the absolute abundance was markedly reduced in dfrA1 , dfrA5 , dfrA7 , aac(3)-1 , CTX-M-1, CTX-M-9, bla-Imp , qnrS , tetM , sul1 , and intl1 genes, which is similar to the data observed by Martins et al [ 73 ] and Raven et al [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of antimicrobials on anaerobic digestion [27,28] and the elimination of ARGs during methane fermentation [29,30] have been explored by many researchers. These problems were also addressed in our previous research [5,31].…”
Section: Introductionmentioning
confidence: 99%